2017
DOI: 10.2174/1871520616666161207143450
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Aminosubstituted Pyrrolopyrimidines with Antiproliferative Activity Against Breast Cancer Cells and Investigation of their Effect Towards the PI3Kα Enzyme

Abstract: Derivatives bearing a specific substitution pattern consisting of 7-phenyl as well as a 2-(4- aminocyclohexylamino) moiety (16c, 16f) display kinase inhibitory activity, elucidated on the basis of molecular simulation studies, which revealed their interaction with the DFG motif of the kinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…E0771 cells were a kind gift of Dr Fernando Rodriguez-Serrano (University of Granada) and were grown as described previously [ 46 ]. Cell toxicity was measured by the MTT assay [ 44 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…E0771 cells were a kind gift of Dr Fernando Rodriguez-Serrano (University of Granada) and were grown as described previously [ 46 ]. Cell toxicity was measured by the MTT assay [ 44 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…This marker is of utmost importance, and there are currently clinical studies evaluating the activity of some inhibitors of this pathway ( 77 ). Recently, it was reported that a group of compounds derived from pyrrolo pyrimidines have activity on PI3K and could act particularly on BCSCs ( 78 ). Another study found that fisetin, a dietary flavonoid, alone or in combination with 5-FU, affects tumorigenesis in the mammalian intestine.…”
Section: Natural Products In the Control Of Bcsc And The Induction Ofmentioning
confidence: 99%